SLCO2B1 genetic polymorphisms in a Korean population: pyrosequencing analyses and comprehensive comparison with other populations - Kim, Kyoung-Ah; Joo, Hyun-Jin; Lee, Hae-Mi; Park, Ji-Young (Molecular biology reports, 2013)
SLCO2B1, also known as OATP2B1 (Organic Anion Transporter) or OATP-B or SLC21A9, is an organic anion uptake transporter that is encoded by the SLCO2B1 gene. In this study we assessed the frequencies of SLCO2B1 polymorphisms in a Korean population using newly developed pyrosequencing methods and compared their frequencies with those in other ethnic groups. We developed pyrosequencing methods to identify the following six SLCO2B1 non-synonymous polymorphisms: c.1175C > T (rs1621378), c.1457C > T (rs2306168), c.43C > T (rs56837383), c.935G > A (rs12422149), c.601G > A (rs35199625) and c.644A > T (rs72559740). The allele frequencies of these polymorphisms were analyzed in 227 Korean subjects. The allele frequencies of SLCO2B1 polymorphisms in the population tested were as follows: 0.0 for c.1175C > T, c.43C > T and c.644A > T; 0.2687 for c.1457C > T; 0.4273 for c.935G > A; and 0.0727 for c. 601G > A. Even though the allele frequencies of the c.1175C > T and c.1457C > T polymorphisms were comparable to those in Japanese subjects, the frequencies in this Korean population differed from those in other ethnic groups. The developed pyrosequencing methods are rapid and reliable for detecting non-synonymous SLCO2B1 polymorphisms. Large ethnic differences in the frequency of SLCO2B1 genetic polymorphisms were noted among ethnic groups. The SLCO2B1 polymorphisms at c.1175C > T, c.43C > T and c.644A > T were not found in the Korean population while c.1457C > T, c.935G > A and c.601G > A exhibited mostly higher frequencies in Koreans compared with Finnish, Caucasian and African-American populations.